(untitled) (Scientific journal of the Fergana State University, 2025)
The aim of this article is to study in detail the chemical composition of Helma and Helba plants and to reveal new scientific data related to their medicinal properties. The results of these studies serve to enrich the knowledge in the field of pharmaceutics and biology and help to expand the significance of these plants as medicinal and food. The importance of Helma plant in the history of medicine, the latest achievements in phytochemistry, as well as its therapeutic, cosmetic and culinary uses are described in detail. The main bioactive components of the plant include essential oils, bitter sesquiterpene lactones, flavonoids, azulenes, phenolic acids, tannins and lignans. Also, the amount of carbohydrates in Helba and Helma plant seeds was determined using an Agilent 1100 chromatograph and analyzed on a scientific basis.